THE STUDY OF DIAGNOSTICS AND PREVENTION OF PATHOPHYSIOLOGICAL PARAMETERS AFTER MODERN TREATMENT OF PURULENT-NECROTIC PROCESSES IN DIABETIC FOOT SYNDROME - Ulugbek Y.Ergashev; Adkhamjon R. Zokhirov; Khojimurod I. Ernazarov; Ravshankhuja R. Minavarkhyjayev; Nodir M. Malikov (Central Asian Journal of Medicine, 2023)
Study of the effect of the new drug "Rheomannisol" on vital organs, taking into account of diagnostics and prevention of pathophysiological aspects in the complex treatment of experimental diabetic foot syndrome.